IDENTIFICATION OF VOLATILE COMPOUNDS, FREE AMINO ACIDS THROUGH CHROMATOGRAPHY AND SENSORY PROPERTIES OF THE PASTA FILATA CHEESES KNOWN AS MOMPOSINO - LONDOÑO O., Myriam; SEPÚLVEDA V., José U.; HIGUERA M., Victor (Vitae, 2011)
The cheese known as Momposino is a Colombian variety of pasta filata cheese. For this investigation, several cheese-production technologies were identified as follows: techniques 1 and 2, for cheeses elaborated from raw milk (such as autochthonous cheeses): technique 3, for cheeses made with pasteurized milk and with a culture; and technique 4, for cheeses made with raw milk. Volatile compounds and free amino acids were examined through chromatography and sensory evaluation tests performed by the members of laboratory. Cheeses made with techniques 1 and 2 presented more volatile compounds (with 60 and 73 respectively) than the cheeses made with technique 3 (for which 52 volatile compounds were found), and the ones made with technique 4 (which presented 40 volatile compounds). The fat content for cheeses from Technique 1 was 29.8%, 30% for cheeses from Technique 2, 27% for cheeses from Technique 3, and 25% for the ones made with Technique 4. These results lead to conclude that the higher the fat content is, the higher the volatile compound production will be. The volatile profiles that were found include acids, alcohols, hydrocarbons and esters. Through the Thin Layer Chrograthography test, it was found that cheese proteins spread to the following amino acids: arginine, valine, tryptophan, histidine, threonine, lysine, tyrosine, alanine, and cysteine. In the cheeses from all treatments, the most outstanding flavor was the acid flavor, and in the most outstanding texture was the elastic texture. No significant differences were found in the sensory evaluation, for the free amino acids (p>0.05), but free fatty acids and fat did show significant differences (p<0.05).